KONTRIBUSI DINAS PEMBERDAYAAN PEREMPUAN PERLINDUNGAN ANAK, PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA DALAM PENANGANAN DAMPAK DARI PERKAWINAN ANAK DI KABUPATEN SLEMAN - Nurmalinda, Putri Ayu; Rozak, Fakih Abdul (Fakultas Agama Islam UNISMA, 2024)
Marriage dispensation in Sleman Regency has continued to increase since 2019 and can only be suppressed in 2023. Applications for marriage dispensation by children are dominated by children aged 18 years and the most applications come from Mlati District with a total of 105 cases of applications in the last 5 years. The most common reason for applying for a marriage dispensation is because a pregnancy has occurred outside of marriage. The purpose of this study is to determine the concept map and handling of the impact of marriage dispensation cases in Sleman Regency, with the focus of the problem being how the marriage dispensation map is in Sleman Regency and what efforts are made to handle the impact of marriage dispensation cases in Sleman Regency. This study uses a qualitative method with a case study approach. Data collection through the interview process and information comes from the Sleman Regency Religious Court and the Department of Women's Empowerment and Child Protection, Population Control and Family Planning (DP3AP2KB). The results of the study are that the Department of Women's Empowerment and Child Protection, Population Control and Family Planning (DP3AP2KB) service continues to strive to assist perpetrators of child marriage so that negative impacts can be reduced and children's readiness to face family life is better and more mature. The Women's Empowerment and Child Protection, Population Control and Family Planning Service (DP3AP2KB) of Sleman Regency continues to make various efforts to handle the impacts that arise as a result of granting marriage dispensation requests, such as socialization regarding the impacts of child marriage, socialization regarding the dangers of pregnancy at a young age, socialization and assistance for mothers and babies, and collaborating with job training institutions to teach parents to be ready to face married life. However, the reason for the marriage is not something that can be justified and understood on an ongoing basis. Keywords: Child Marriage, Legal Impact, Social Impact. Abstrak Dispensasi Perkawinan di kabupaten Sleman sejak tahun 2019 terus mengalami kenaikan dan baru bisa ditekan pada tahun 2023, Pengajuan Dispensasi Perkawinan oleh anak di di dominasi anak usia 18 tahun dan terbanyak pengajuan berasal dari kecamatan mlati dengan total pengajuan dalam 5 tahun terakhir sebanyak 105 kasus. Alasan pengajuan dispensasi Perkawinan paling banyak adalah karena telah terjadi kehamilan di luar nikah. Tujuan penelitian ini adalah untuk mengetahui peta konsep dan penanganan dampak perkara dispensasi Perkawinan di kabupaten sleman, dengan fokus masalah adalah bagaimana peta persebaran dispensasi Perkawinan di Kabupaten Sleman serta apa saja upaya penanganan dampak perkara dispensasi Perkawinan di kabupaten sleman. Penelitian ini menggunakan metode kulitatif dengan pendekatan studi kasus. Pengumpulan data melalaui proses wawancara dan informasi bearasal dari pengadilan agama kabupaten sleman dan Dinas Pemberdayaan Perempuan dan Perlindungan Anak, Pengendalian Penduduk dan Keluarga Berencana (P3AP2KB). Hasil penelitian adalah dinas p3ap2kb terus berupaya untuk mendampingi para pelaku Perkawinan anak agar dampak-dampak buruk bisa ditekan dan kesiapan anak untuk menghadapi kehidupan rumah tangga lebih baik dan matang. Dinas Pemberdayaan Perempuan dan Perlindungan Anak, Pengendalian Penduduk dan Keluarga Berencana (P3AP2KB) kabupaten sleman terus melakukan berbagai upaya untuk menangani dampak-dampak yang muncul akibat dari pengabulan permohonan dispensasi Perkawinan seperti sosialisasi mengenai dampak Perkawinan anak, sosialisasi mengenai bahaya hamil di usia muda, sosialisasi dan pendampingan pada ibu dan bayi, maupun bekerjasama dengan lembaga pelatihan kerja untuk mengajarkan para orang tua agar siap untuk menghadapi kehidupan berumah tangga. namun alasan terjadinya Perkawinan bukan sesuatu yang bisa dihalalkan dan dimaklumi secara berkelanjutan. Kata kunci: Perkawinan Anak, Dampak Hukum, Dampak Sosial.